2016
DOI: 10.1118/1.4962933
|View full text |Cite
|
Sign up to set email alerts
|

Investigating deformable image registration and scatter correction for CBCT‐based dose calculation in adaptive IMPT

Abstract: International audiencePurpose:This work aims at investigating intensity corrected cone-beam x-ray computed tomography (CBCT) images for accurate dose calculation in adaptive intensity modulated proton therapy (IMPT) for prostate and head and neck (H&N) cancer. A deformable image registration (DIR)-based method and a scatter correction approach using the image data obtained from DIR as prior are characterized and compared on the basis of the same clinical patient cohort for the first time.Methods:Planning CT (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(192 citation statements)
references
References 45 publications
(46 reference statements)
9
183
0
Order By: Relevance
“…Due to the considerable interfractional anatomical differences between pCT and daily CBCT in the prostate region, CBCTcor was used as reference for data evaluation. The accuracy of CBCTcor has been demonstrated in earlier studies, even in the context of proton therapy 24,25 …”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Due to the considerable interfractional anatomical differences between pCT and daily CBCT in the prostate region, CBCTcor was used as reference for data evaluation. The accuracy of CBCTcor has been demonstrated in earlier studies, even in the context of proton therapy 24,25 …”
Section: Methodsmentioning
confidence: 89%
“…Several papers have investigated intensity correction based on the planning CT, for example, through Monte Carlo simulation of the cone‐beam CT acquisition process, 9,20,21 or through raytracing and filtering 22–24 . These methods have been shown to reproduce the planning CT Hounsfield units (HU) to sufficient accuracy for both photon and proton dose calculation 25 . They are, however, limited by the time it takes to correct the images, which is more than 10 minutes for the raytracing‐based methods, or several hours for the Monte Carlo‐based methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation in our study was the low soft tissue contrast of CBCT; as shown for the prostate,26 this prevents accurate deformable image registration for soft tissues, such as pancreas and surrounding organs. For calculated overall dose distributions, the effect of inaccurate soft tissue registration is very limited due to the limited difference in HU between the different soft tissues.…”
Section: Discussionmentioning
confidence: 98%
“…In (e) an in‐room equivalent control CT acquired 1 day after the CBCT was used to calculate the adapted plan and serves as reference. Figure adapted with permission from Kurz et al …”
Section: Beyond Anatomy‐based Positioningmentioning
confidence: 99%